Cadar dalam Ruang Publik: Analisis Wacana Kritis Norman Fairclough pada Instagram @Aisyiyahpusat - Nikmah Lubis (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
The study entitled "Veils in Public Spaces: Norman Fairclough's Critical Discourse Analysis on Instagram @ Aisyiyahpusat" was conducted to find out the message in the linguistic aspects contained in @Aisyiyah's post. This research was conducted using library research methods from studying data sourced from books, accredited journal articles and online news. Then it is studied through Norman Fairclough's critical discourse analysis from looking at social practices through the dimensions of text and social practices that underlie the text and revealing the social realities that make the discourse emerge. This study describes a vehicle that uses veil in public spaces with a Government Regulation. Then accompanied from the role of the authorities by issuing Fatwa Online through the @AisyiyahPusat Instagram account. After conducting research it was found that the Fatwa issued by Muhammadiyah used "soft" language by providing metaphors in the form of a narrative, not using words that would put veil users or organizations with similar understandings into a corner. In conclusion, the use of words in the text when issuing a fatwa has a major effect on the representation of society